Microvessel networks in pre-formed in artificial clinical grade dermal substitutes in vitro using cells from haematopoietic tissues - Athanassopoulos, A; Tsaknakis, G; Newey, S; Harris, A; Kean, J; Tyler, M; Watt, S (2012)
Forming a microcirculation is critical for vascularisation of artificial skin substitutes. One strategy to improve speed of grafting is to pre-form microvascular networks in the substitute before applying to a wound. For clinical application, this requires sufficient functional endothelial cell numbers. In vitro endothelial colony forming cells (ECFCs) derived cells were expanded from cord and adult blood donations and co-cultured with human dermal fibroblasts or bone marrow mesenchymal stem/stromal cells to form microvascular networks in the presence or absence of dermal substitutes which are in clinical use. The number of endothelial cells generated ranged from 1.03 × 10 9 to 2.18 × 1011 from 10 adult blood donations and 1 × 1012 to 1.76 × 1013 from 6 cord blood units after 50 days in culture. Two adult donations failed to generate ECFCs. Both cord and adult blood cells formed 2D microvascular networks in vitro, although there was a significant difference in the functional capacity of adult and cord blood ECFCs. While co-culture of the latter within dermal substitutes Matriderm or Integra demonstrated the formation of 3D microvascular networks penetrating 100 μm, enhanced expansion, while maintaining functional capacity, of adult blood cells is required for fully pre-vascularising the clinical grade acellular dermal substitutes used here prior to applying these to burns. © 2012 Elsevier Ltd and ISBI.